Protective Role of Magnetic Treatments for Seeds and Sea Water on Germination of Triticum Aestivum L. (Wheat) - Widad El-Mugrbi; Jamila Bashasha; Seham Mohammeda (AlQalam Journal of Medical and Applied Sciences, 2022)
Objectives. The present study was conducted to evaluate whether treating sea water or seeds with a magnetic field (14500 Gaus) can improve the germination growth of three cultivars wheat plant Triticum aestivum L. Methods. The magnetic treatment involved, exposing the seeds to different periods of magnetization (0, 15, 30 and 45 min) and passing of sea water levels (0, 20, 50 and 80%) through magnetic field (14500 Gaus). Results. Using magnetic stimulated seeds or irrigation with magnetized sea water were better compared to the non-treated of three wheat cultivars. The results indicated also that magnetized irrigation water did not affect in germination percentage but the magnetic pre-sowing seed treatment led to an increase in germination percentage, especially under salinity 80% and 45min, compared to the non- treated seeds. Conclusion. Magnetic treatment of saline water or seeds improved seed germination, vigor index, shoot and root length of three wheat cultivars under saline conditions.